To study the clinical and radiological outcome of treatment with leukocyte depleted platelet rich plasma and Hyaluronic Acid injections in early to moderate primary osteoarthritis (International Journal of Environmental Sciences, 2025)
Introduction: Osteoarthritis (OA) of the knee is a prevalent degenerative condition characterized by progressive cartilage deterioration and associated symptoms that significantly impact quality of life. Traditional treatments often provide only temporary relief with limited disease-modifying effects. Emerging biological treatments such as platelet-rich plasma (PRP) and hyaluronic acid (HA) injections have shown promise, but comparative evidence regarding their clinical and radiological efficacy remains limited, particularly for combined therapy approaches using leukocyte-depleted PRP formulations.Objectives: To evaluate the clinical and radiological outcomes of treatment with combined leukocyte-depleted platelet-rich plasma (LP-PRP) and hyaluronic acid (HA) injections versus placebo in patients with early to moderate primary knee osteoarthritis over a 12-month follow-up period.Case: In this prospective randomized controlled trial, 60 patients with early to moderate knee OA (Kellgren-Lawrence grades 1-3) were randomly allocated to either the treatment group receiving combined LP-PRP and HA injections (n=30) or the placebo group receiving saline injections (n=30). Patients were assessed at baseline, 3, 6, and 12 months using Visual Analog Scale (VAS) for pain, Knee Injury and Osteoarthritis Outcome Score (KOOS) for functional outcomes, International Knee Documentation Committee (IKDC) score, and MRI Osteoarthritis Knee Score (MOAKS) for cartilage assessment.Results: Despite having higher baseline pain scores and more severe radiographic OA, the treatment group demonstrated significantly better outcomes across all clinical parameters at 12 months compared to the placebo group. The treatment group showed a 67.8% reduction in VAS pain scores (6.53 to 2.1) compared to a worsening in the placebo group (5.17 to 5.88). All KOOS subscales showed significantly greater improvement in the LP-PRP group, with improvements ranging from 60.5% to 72.5% from baseline. MOAKS Cartilage assessment revealed slight improvement in the treatment group (1.23 to 1.10) while the placebo group deteriorated (1.27 to 1.83, p=0.001).Conclusion: Combined LP-PRP and HA injections provide superior clinical and radiological outcomes compared to placebo for patients with early to moderate knee OA over a 12-month follow-up period.